SUN RAY AND COLOR THERAPY: सूर्य किरण और रंग चिकित्सा - Vyas, Snehalata (International Journal of Research -GRANTHAALAYAH, 2014)
The entire body of beings is colorful. All the components of the body have different colors. All the cells of the body are also colored. If any part of the body becomes ill, then there is an imbalance of colors along with its chemical substances. Color therapy balances those colors. If you feel a lack of energy, you get a lack of confidence, if the thinking is not clear then color therapy can help you. Colors have a profound effect on the brain on our mind. This color strength has also made it useful for healing. There are many diseases for which color is used for treatment. Due to these characteristics, it has been named "Color Therapy". प्राणियों का सम्पूर्ण शरीर रंगीन है। शरीर के समस्त अवयवों का रंग अलग-अलग है। शरीर की समस्त कोषिकायें भी रंगीन है। शरीर का कोई अंग बीमार होता है तो उसका रासायनिक द्रव्यों के साथ-साथ रंगो का असंतुलन हो जाता है। रंग चिकित्सा उन रंगो को संतुलित कर देती है। आप ऊर्जा की कमी महसूस करते है आत्मविष्वास में कमी पाते है, सोच स्पष्ट नहीं हो पाती है तो रंग चिकित्सा आपकी सहायता कर सकती है। रंगो का हमारे मन पर मस्तिष्क पर गहरा असर पड़ता है। रंगो की इस ताकत ने उपचार के लिए भी उपयोगी बना दिया है। कई बिमारियाँ है जिनके उपचार के लिए रंगो का इस्तेमाल किया जाता है। इन खूबियों के कारण इसे ‘‘कलर थेरेपी‘‘ यानी रंग चिकित्सा का नाम दिया गया है।